Recoveries of Grey Seals Halichoerus grypus (Fabricius) tagged along the Norwegian coast - Øystein Wiig; Nils Øien (Fauna Norvegica)
A total of 1040 Grey Seals have been tagged along the Norwegian coast in the period from 1975 to 1986. Most of them (985) have been tagged at Froan on the coast of Sør-Trøndelag. Ninetythree of the tagged seals have been recovered. The majority of these (62) have been found dead on land or in fishing gears during their first year of life, and the total recovery rate during the first year is 6.3%. The pups disperse widely. The furthest dispersals recorded on the Norwegian coast during the first year after tagging have been 380 km to the south and 320 km to the north of Froan. In addition, one pup tagged at Froan was recovered 82 days later on the northwestern coast of Denmark. Most of the recoveries are, however, recorded less than 100 km from the tagging locality. Nine mature seals have been recovered during the breeding season. Five of these have been caught at their place of birth and the other four have been caught 20 to 80 km away. It is concluded that there are no data implying that the Froan stock of Grey Seals is recruiting other breeding stocks on the Norwegian coast.